Investigating the performance of time-constrained clustering of multi-modal chemical process data - Olivier, Jacobus Frederik (Stellenbosch : Stellenbosch University, 2025)
Olivier, J. F. 2025. Investigating the performance of time-constrained clustering of multi-modal chemical process data. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5df85a8e-234d-4a22-90ac-7ce2b0b6f59d